Total Rainbow Connection Number Of Shackle Product Of Antiprism Graph (〖AP〗_3) (Jurnal Matematika, Statistika dan Komputasi, 2023)
Function if  is said to be k total rainbows in , for each pair of vertex  there is a path called  with each edge and each vertex on the path will have a different color. The total connection number is denoted by trc  defined as the minimum number of colors needed to make graph  to be total rainbow connected. Total rainbow connection numbers can also be applied to graphs that are the result of operations. The denoted shackle graph  is a graph resulting from the denoted graph  where t is number of copies of G. This research discusses rainbow connection numbers rc and total rainbow connection trc(G) using the shackle operation, where  is the antiprism graph . Based on this research, rainbow connection numbers rc shack , and total rainbow connection trc shack for .
Keywords: Total Rainbow Connection; Shackle; Antiprism Graph